Relationship between sleep habits and academic performance in university Nursing students - Juana Inés Gallego-Gómez; María Teresa Rodríguez González-Moro; José Miguel Rodríguez González-Moro; Tomás Vera-Catalán; Serafín Balanza; Agustín Javier Simonelli-Muñoz; José Miguel Rivera-Caravaca (BMC, 2021)
Abstract Background Sleep disorders are composed of a group of diseases of increasing prevalence and with social-health implications to be considered a public health problem. Sleep habits and specific sleep behaviors have an influence on the academic success of students. However, the characteristics of sleep and sleep habits of university students as predictors of poor academic performance have been scarcely analyzed. In the present study, we aimed to investigate sleep habits and their influence on academic performance in a cohort of Nursing Degree students. Methods This was a cross-sectional and observational study. An anonymous and self-administered questionnaire was used, including different scales such as the 'Morningness and Eveningness scale', an author-generated sleep habit questionnaire, and certain variables aimed at studying the socio-familial and academic aspects of the Nursing students. The association of sleep habits and other variables with poor academic performance was investigated by logistic regression. The internal consistency and homogeneity of the 'sleep habits questionnaire' was assessed with the Cronbach's alpha test. Results Overall, 401 students (mean age of 22.1 ± 4.9 years, 74.8 % females) from the Nursing Degree were included. The homogeneity of the 'sleep habits questionnaire' was appropriate (Cronbach's alpha = 0.710). Nursing students were characterized by an evening chronotype (20.2 %) and a short sleep pattern. 30.4 % of the Nursing students had bad sleep habits. Regarding the academic performance, 47.9 % of the students showed a poor one. On multivariate logistic regression analysis, a short sleep pattern (adjusted OR = 1.53, 95 % CI 1.01-2.34), bad sleep habits (aOR = 1.76, 95 % CI 1.11-2.79), and age < 25 years (aOR = 2.27, 95 % CI 1.30-3.98) were independently associated with a higher probability of poor academic performance. Conclusions Almost 1/3 of the Nursing students were identified as having bad sleep habits, and these students were characterized by an evening chronotype and a short sleep pattern. A short sleep pattern, bad sleep habits, and age < 25 years, were independently associated with a higher risk of poor academic performance. This requires multifactorial approaches and the involvement of all the associated actors: teachers, academic institutions, health institutions, and the people in charge in university residences, among others.